Lanthanum in vitro control of Alternaria solani and induction resistance mechanism against blight tomato plant - Solino, Antônio Jussiê da Silva; Oliveira, Juliana Santos Batista; Cesnik, Sergio Augusto; Schwan-Estrada, Kátia Regina Freitas (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Rare earth elements have been tested in control of plant diseases. Lanthanum (La) was tested in the control of Alternaria solani (in vitro) and tomato early blight (in vivo) using the concentration 0; 0.1; 0.2; 0.4 and 0.8 g L-1. In vitro, the concentration were diluted in V8 culture medium and evaluated for mycelial growth rate index (MGRI) and pathogen sporulation. In vivo, 24 hours after the application of concentration was inoculate the pathogen and 24 hours after the inoculation, leaflets were collected for quantification, the specific catalytic activity and guaiacol peroxidase. The severity of tomato early blight were also analyzed. As 0.27 and 0.28 g L-1 reduces 28% and 50% the MGRI and the sporulation, respectively. Peroxidase and catalase activity was increased by 298% and 151% in tomato treated with 0.5 and 0.4 g L-1de La, respectively. In vivo reduces AUDPC 70% when was applied 0.27 g L-1 La. Lanthanum can be used as resistance inducer in controlling tomato early blight.